Ichneumonidae (Hymenoptera) associated with xyelid sawflies (Hymenoptera, Xyelidae) in Mexico - Khalaim, Andrey I.; Ruíz Cancino, Enrique (2017)
Se describen dos especies de Ichneumonidae, Gelanes horstmanni Khalaim, sp. n. (Tersilochinae) e Idiogramma elbakyanae Khalaim sp. n. (Tryphoninae), de un bosque de pinos a 2800–2900 msnm en el Estado de Tlaxcala en la zona central de México; una tercera especie, I. comstockii (Ashmead), se reporta del Estado de Nuevo León en el noreste de México. Los géneros Gelanes Horstmann e Idiogramma Förster están asociados con moscas sierra xyélidas (Xyelidae), ambos géneros y la tribu Idiogrammatini de la subfamilia Tryphoninae se reportan para México por primera vez. Se elaboró una clave para la identificación de las dos especies de Idiogramma que ocurren en México. ABSTRACT Two species of ichneumon wasps (Ichneumonidae), Gelanes horstmanni Khalaim, sp. n. (Tersilochinae) and Idiogramma elbakyanae Khalaim sp. n. (Tryphoninae), are described from the pine forest at 2800– 2900 m from the State of Tlaxcala in Central Mexico; a third species, I. comstockii (Ashmead), is found to occur in the State of Nuevo León in Northeast Mexico. The genera Gelanes Horstmann and Idiogramma Förster are associated with xyelid sawflies (Xyelidae), and both, as well as the tryphonine tribe Idiogrammatini, are recorded from Mexico for the first time. An identification key to the two Idiogramma species occurring in Mexico is provided.